Integrative assessment of the ecological risk of heavy metals in a South American estuary under human pressures - Truchet, Daniela María (2021)
Biomonitoring of heavy metal pollution through the use of biomarkers could be a difficult task since the organisms´ physiological changes could shift regarding natural factors (i.e., the season of the year) and due to the anthropogenic pressures of the environment. In the Southwest Atlantic Ocean, where most industrial and developing countries are settled, it is essential to address these concerns to generate information for the stakeholders and monitoring programs that aim to use biochemical biomarkers as early warning signals to detect heavy metal pollution. The present study intended to determinate the heavy metal concentrations in sediments and the hepatopancreas of the crab species Neohelice granulata as well as the ecological risk through the use of biomarkers and geochemical indices in sites with different anthropogenic pressures of the Bahía Blanca estuary (SW Atlantic Ocean) during the warm and cold season. The results showed low to moderate heavy metal pollution in the sediments by Cu with possible effects on the biota in a site with sewage waters? discharges. Except for GST that was explained by Cd, the biomarkers employed were not useful to assess spatial heavy metal pollution, and they might be ruled out by physiological seasonal variations rather than anthropogenic constraints, or another type of pollutants in the area.